Rani the enchanted dragon - Mara, Maddy (Mara, Maddy. Dragon girls., 2024)
"In the Magic Forest, ordinary girls transform into powerful dragons. As Dragon Girls, they can soar above the treetops, breathe magical bursts of fire, and roar loud enough to shake the ground. Rani the Enchanted Dragon is facing one of the biggest challenges the Magic Forest has ever seen. A new villain has an evil plot in mind. She's planning to kidnap all the adorable animals who usually help Dragon Girls complete their quests. Without these forest friends, this special place could be lost forever!"--Amazon.com.